The Effect of Economic Growth, Population and Unemployment on HDI - Wahyuningrum, Febrianti; Soesilowati, Etty (Universitas Negeri Semarang, 2021)
East Java Province is a province in Indonesia, which has the potential to develop. Provincial HDI has increased every year, but the HDI of East Java Province is quite low compared to the HDI of other provinces in Java. The rate of economic growth that occurred in East Java Province decreased. The existence of the unemployment rate causes the prosperity of the community to be not optimal, while the purpose of human development is to create community welfare. The data used in this research is using secondary data. This study uses the ordinary least square method with multiple regression analysis. This study uses a combination of time series data from 2014-2018 and a cross section of 38 districts or cities in East Java Province. The variables used are Economic Growth Rate, Population and Open Unemployment Rate. Based on the research results, it can be concluded that the population has a significant effect on the human development index (HDI) and the rate of economic growth and the open unemployment rate does not significantly affect the Human Development Index (HDI). Provinsi Jawa Timur merupakan Provinsi di Indonesia tepatnya di Pulau Jawa yang mempunyai potensi untuk berkembang. IPM Provinsi mengalami peningkatan setiap tahunnya, namun IPM Provinsi Jawa Timur cukup rendah dibandingkan dengan IPM Provinsi lain yang ada di Pulau Jawa. Laju pertumbuhan ekonomi yang terjadi pada Provinsi Jawa Timur terjadi penurunan. Adanya Tingkat pengangguran menyebabkan kemakmuran masyarakat tidak maksimal sedangkan tujuan adanya pembangunan manusia adalah untuk menciptakan kesejahteran masyarakat. Data yang digunakan dalam penelitian ini adalah menggunakan data sekunder. Penelitian ini menggunakan metode ordinary least square dengan analisis regresi berganda. Penelitian ini menggunakan gabungan antar data time series yaitu dari tahun 2014-2018 dan cross section 38 kabupaten atau kota di Provinsi Jawa Timur. Variabel yang digunakan adalah Laju Pertumbuhan Ekonomi, Jumlah Penduduk dan Tingkat Pengangguran Terbuka. Berdasarkan hasi penelitian, dapat diambil kesimpulan bahwa Jumlah Penduduk memiliki pengaruh signifikan terhadap indeks pembangunan manusia (IPM) dan laju pertumbuhan ekonomi dan tingkat pengangguran terbuka tidak berpengaruh secara signifikan terhadap Indeks Pembangunan Manusia (IPM).